MANAJEMEN PEMBINAAN PEDAGANG KAKI LIMA OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN DI KAWASAN PASAR TERATAI HIGIENIS MADANI KOTA PEKANBARU - Sucy Vira Mita; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Street vendors are economic activities that operate in the informal sector which have a negative and positive impact. Pekanbaru City Government overcomes the problem of street vendors who sell on the shoulder of the road by carrying out fostering. At present, fostering of street vendor is being carried out in stages, one of which is by building the Teratai Higienis Madani. The purpose of this research was to find out the fostering management of street vendors by Trade and Industry Agency in Teratai Higienis Madani Market Area Pekanbaru City and the inhibiting factors of management of street vendors. The research uses the theory of management function concepts according to Terry dalam (Torang, 2016) which has an indicator of Planning, organizing, actuating, and controlling. This research method uses a qualitative method of case study approach, with data collection techniques including: observation, interviews, and documentation. The research informants were selected through purposive sampling and snowball sampling techniques. Research results show that the fostering management of street vendors is not optimal so that traders do not last long selling in the Market. The inhibiting factors in the Management of Coaching of Street Vendors are public policy, control, participation of traders, facilities and infrastructure, budget. Suggested as the government can optimize the management of the management of street vendors by more assertive and active in controlling and fostering.Keyword: Management, Fostering, Street Vendors